Exploring the Experiences of Women in Topmost Management Positions at the University of Cape Coast - Aggrey, Nancy (University of Cape Coast, 2025)
At present, most organizations do not have a majority of women in top managerial positions even though the proportion of women in managerial roles has steadily increased over time. This research was conducted against the backdrop of the continued disparity in gender at the top executive leadership positions in Ghana‘s educational institutions. Investigating the reasons for this, and how the small percentage of women in these roles were able to reach the topmost positions was the goal of the present study. The study explored the unique experiences of women in topmost management positions at the University of Cape Coast, focusing on the distinct characteristics they possess, their interactions with their colleagues, causes of their underrepresentation, and their success stories. The research used a case-study design with participants sampled purposively. In all, 4 participants (respondents) were interviewed. Also, through interviews and qualitative analysis, the researcher aimed to uncover the strategies they employed to navigate the multifaceted challenges they faced. The study revealed that women occupying topmost management positions possessed traits like emotional intelligence, good communication and interpersonal skills. They also adopted leadership styles such as the democratic or blended approach. The study also revealed that the women had a good relationship with their colleagues and direct reports, and faced some challenges along their career paths. These challenges included combining work and family responsibilities. While they found ways to overcome challenges they encountered, they believed such factors as stereotyping, tradition and education were some causes of underrepresentation. The study, therefore, recommended that as higher education institutions work towards creating an enabling and inclusive environment for both women and men to work peacefully, tailored leadership programmes should be offered to empower women the more. Finally, female peer networks should be strengthened, and male leaders should be engaged as allies to help promote gender diversity and inclusive leadership.
xiii, 148p;, ill
Keywords: Career progression Direct report Experiences Higher education administration Topmost management positions Underrepresentation Women